Insights on the Evolutionary Genomics of the Blautia Genus: Potential New Species and Genetic Content Among Lineages - Maturana, José Luis; Cárdenas, Juan P. (Frontiers in Microbiology, 2021)
Blautia, a genus established in 2008, is a relevantly abundant taxonomic group present in the microbiome of human and other mammalian gastrointestinal (GI) tracts. Several described (or proposed) Blautia species are available at this date. However, despite the increasing level of knowledge about Blautia, its diversity is still poorly understood. The increasing availability of Blautia genomic sequences in the public databases opens the possibility to study this genus from a genomic perspective. Here we report the pangenome analysis and the phylogenomic study of 225 Blautia genomes available in RefSeq. We found 33 different potential species at the genomic level, 17 of them previously undescribed; we also confirmed by genomic standards the status of 4 previously proposed new Blautia species. Comparative genomic analyses suggest that the Blautia pangenome is open, with a relatively small core genome (∼ 700–800 gene families). Utilizing a set of representative genomes, we performed a gene family gain/loss model for the genus, showing that despite terminal nodes suffered more massive gene gain events than internal nodes (i.e., predicted ancestors), some ancestors were predicted to have gained an important number of gene families, some of them associated with the possible acquisition of metabolic abilities. Gene loss events remained lower than gain events in most cases. General aspects regarding pangenome composition and gene gain/loss events are discussed, as well as the proposition of changes in the taxonomic assignment of B. coccoidesTY and the proposition of a new species, “B. pseudococcoides.”